Taser Use in Scotland: a Qualitative Study of Police Officer and Community Perspectives - Deuchar, Ross (European journal on criminal policy and research, 2025)
This study delves into police and public views on Taser deployment in Scotland, coinciding with its most significant introduction. Using comprehensive qualitative data, we highlight findings from interviews with 13 Specialized Training Officers (STOs), responses from 88 police officers, and focus groups involving 66 community members in western Scotland. Findings indicate officers largely perceive Tasers as an effective deterrent against violent crime, enhancing community safety. However, while the general public is predominantly supportive, concerns arise regarding potential misuse against youth and risks posed to the vulnerable. These apprehensions cast doubts over further Taser expansions. The study underscores key considerations for future policies, operational practices, and research avenues.